Electronically Double‐Layered Metal Boride Hollow Nanoprism as an Excellent and Robust Water Oxidation Electrocatalysts. Issue 13 (12th February 2019) - Han, HyukSu; Hong, Yu‐Rim; Woo, Jungwook; Mhin, Sungwook; Kim, Kang Min; Kwon, Jiseok; Choi, Heechae; Chung, Yong‐Chae; Song, Taeseup
Abstract: Metal–metalloid compounds have been paid much attention as new high‐performance water oxidation catalysts due to their exceptional durability for water oxidation in alkaline media originating from the multi‐dimensional covalent bonding of the metalloid with the surrounding metal atoms. However, compared to the excellent stability, a relatively low catalytic activity of metal‐metalloids often limits their practical application as high‐performance water oxidation catalysts. Here, for the first time, disclosed is a novel self‐templating strategy combined with atomic layer deposition (ALD) to design the electrochemically active and stable quaternary metal boride (vanadium‐doped cobalt nickel boride, VCNB), hollow nanoprism by inducing electronic double layers on the surface. The incorporation of V in a double‐layered structure can substantially increase the number of surface active sites with unsaturated electronic structure. Furthermore, the induced electronic double layers of V can effectively protect the dissolution of the surface active sites. In addition, density functional theory (DFT) calculations reveal that the impressive water oxidation properties of VCNB originate from the synergetic physicochemical effects of the different metal elements, Co and B as active sites, Ni as a surface electronic structure modifier, and V as a charge carrier transporter and supplier. Abstract : Electronically double‐layered structure in quaternary metal–metalloid hollow nanoprism can substantially enhance water oxidation activity as well as stability of metal–metalloid in alkaline media.